Data and Management Traffic of IEEE 802.15.4 ZigBee-Based WSN - Baqer , Naseem K.; Abbas , Ali W.; Salih , Bassam A. (International Journal of Advanced Science Computing and Engineering, 2024)
Wireless sensor networks (WSNs) are an amalgam of wireless technologies. They are extensively utilized in numerous industries, including agriculture, medical, and military fields. In the vast majority of cases, these technologies are deployed in monitoring environmental or physical parameters including sound, pressure, and temperature. WSNs employ various technologies, including radio frequency (RF), Wi-Fi, Bluetooth, ZigBee, and Z-Wave. Zigbee in particular has greater potential for energy-savings in long-distance transmissions, and consequently has emerged as the preferred standard for use in WSNs. In Zigbee-assisted networks, the three primary data-communication devices are ZigBee coordinators, routers, and nodes. The coordinator device gathers, stores, and processes the data before forwarding it to the next appropriate node or the base-station. The system model comprises several zones with each zone containing several sensors. Each sensor node transfers data to the master node, which serves as the ZigBee coordinator. The software used for this simulated investigation is the Riverbed Modeler V17.5. This paper examines the data traffic, management traffic, and load performance of the four modelled systems. The findings demonstrate that whereas the number of coordinators has no effect on data traffic, an increase in the number of routers correspondingly increases both the amount of data sent and received. The MAC follows the same pattern.